Effect of heavy-equipment aided environmental nebulization on Aedes aegypti vectors of Dengue, Zika and Chikungunya in SAo Paulo, Brazil - Piovezan, R. [UNESP]; Acorinthe, J. Paulo O.; Visockas, A.; Azevedo, T. S. de; Von Zuben, C. J. [UNESP] (Cambridge Univ Press, 2017)
The control of dengue constitutes a great challenge for public health; however, the methods normally used have shown themselves to be insufficient to keep the indices of infestation of Aedes aegypti under control. Recently, beyond the large number of cases and deaths associated with dengue, new risks have arisen such as those represented by chikungunya fever and Zika. In the light of the great significance of these problems within the public health context, two areas in a municipality in the interior of the State of SAo Paulo, Brazil were selected in 2014. One of them, Bairro Cidade Nova, was submitted to the conventional method of nebulization with portable equipment, and the other, Bairro Jardim Europa, received the application of the insecticide by means of heavy-equipment coupled to the vehicle. During the project, 1355 mosquito eggs were collected, 1105 of them in Bairro Cidade Nova and 205 in Bairro Jardim Europa. After the applications with heavy-equipment in the months of March and April, the number of cases of the disease reported in the month of April for Bairro Jardim Europa was less than half that of Bairro Cidade Nova, which had received the conventional treatment. The nebulization with the heavy-equipment may constitute a viable and effective strategy for achieving better results in the control of Ae. aegypti.
Keywords: Aedes aegypti; vector control; dengue; Zika; chikungunya